AI-Based Plan-Strategy for Implementing the Principles of Corporate Social Responsibility in Small Family Businesses’ Activities - Todorova, Ana; Kostadinova, Irina; Kirova, Milena (European Journal of Sustainable Development, 2025)
The growing importance of corporate social responsibility (CSR) and its evolution from a voluntary concept to a regulatory and strategic requirement pose new challenges for small and medium-sized enterprises (SMEs) that have yet to face it. Family businesses, which constitute the majority of enterprises worldwide and exhibit unique characteristics, including resource efficiency and long-term orientation, will also need to take proactive steps towards the systematic implementation and reporting of CSR. In parallel, artificial intelligence (AI) stands out as a transformative technology with the potential to revolutionise business processes and significantly increase transparency and accountability in reporting environmental, social and governance (ESG) data. This paper proposes an AI-based plan-strategy designed to facilitate and enhance the implementation of CSR principles in small family businesses (SFBs). The strategy is primarily theoretical, with its applicability exploratively tested in a pilot study in a small family winery. Despite the limitations arising from the theoretical nature, limited sample and case study, the development has theoretical applicability by offering a conceptual framework and basis for future research on the synergy between AI, CSR and family business characteristics. From a practical perspective, the strategy provides a guideline. It identifies specific areas where AI can support CSR efforts in SMEs, serving as a starting point for pilot projects and business support. Keywords: corporate social responsibility, artificial intelligence, strategy, family businesses